Camparison between Qualitative and Quantitative Research Approaches: Social Sciences - aida mehrad; Mohammad Hossein Tahriri Zangeneh (Indonesia Prime, 2020)
Nowadays because of the vast of investigations and high level of technology, majority of investigators endeavour to apply appropriate methods in their research; in this case, focusing on research approaches assumed as one of the critical factors in the science world. In research methodology specifically in social science area, two approaches of qualitative and quantitative have been considered more. These approaches assumed as two practical and essential methods in most of investigations. Therefore, the purpose of current literature review is to distinguish the imperative comparison of quantitative and qualitative in the research methodology and determining the brilliant differences between these research factors. Furthermore, realizing the accurate approach and apply it in the correct way in every investigation is super important; then, the researchers endeavour to justify this essential fact for future studies.